2002
DOI: 10.1111/1540-6229.t01-1-00053
|View full text |Cite
|
Sign up to set email alerts
|

The Termination of Commercial Mortgage Contracts through Prepayment and Default: A Proportional Hazard Approach with Competing Risks

Abstract: This article examines the factors driving the borrower's decision to terminate commercial mortgage contracts with the lender through either prepayment or default. Using loan-level data, we estimate prepayment and default functions in a proportional hazard framework with competing risks, allowing us to account for unobserved heterogeneity. Under a strict definition of mortgage default, we do not find evidence to support the existence of unobserved heterogeneity. However, when the definition of mortgage default … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 33 publications
(48 reference statements)
1
42
0
Order By: Relevance
“…On the other hand, their results reveal that initial property income (measured by debt service coverage at origination) is a strong predictor of default. Ciochetti et al [2002] further extend the literature by including contemporaneous measures of LTV and DSC in their empirical analysis. They estimate default and prepayment functions for commercial mortgages using a competing risks proportional hazards model and loan-level data, and find that an asset value-based model alone cannot fully explain default incidence.…”
Section: Recent Developments In Commercial Mortgage Defaultmentioning
confidence: 86%
“…On the other hand, their results reveal that initial property income (measured by debt service coverage at origination) is a strong predictor of default. Ciochetti et al [2002] further extend the literature by including contemporaneous measures of LTV and DSC in their empirical analysis. They estimate default and prepayment functions for commercial mortgages using a competing risks proportional hazards model and loan-level data, and find that an asset value-based model alone cannot fully explain default incidence.…”
Section: Recent Developments In Commercial Mortgage Defaultmentioning
confidence: 86%
“…Gabriel and Nothaft (2001) analyse the duration of rental vacancies in major USA metropolitan areas with ordinary least square regressions. Ciochetti et al (2003a) analyse the factors driving the borrower's decision to terminate commercial mortgage contracts with the lender through either prepayment or default. Data on loans from large USA insurance companies are used.…”
Section: Duration Models In Housing a Reviewmentioning
confidence: 99%
“…For example, increasing volume of studies has shown that it is the contemporaneous loan-to-value ratio (LTV) and debt-service-coverage ratio (DSCR) rather than original LTV and DSCR that determines commercial mortgage default risk 10 (Vandell et al, 1993, Archer et al, 2001, Ambrose and Sanders, 2003, Ciochetti et al 2003, Ciochetti et al 2002, Chen and Deng, 2003and Deng, Quigley and Sanders, 2005.…”
Section: Research Question and Empirical Approachmentioning
confidence: 99%
“…Hazard model has been proven to be a very effective tool to estimate and predict commercial mortgage default probabilities (Vandell, 1993, Huang and Ondrich, 2002, Ciochetti et al, 2002and Chen and Deng, 2003. We follow the literature to include the most important variables such as the intrinsic value of call exercise and the intrinsic value of put exercise (contemporaneous LTV) as our covariates.…”
Section: Research Question and Empirical Approachmentioning
confidence: 99%